Autophagy inhibition blunts PDGFRA adipose progenitors' cell-autonomous fibrogenic response to high-fat diet. Issue 12 (1st December 2020) - Marcelin, Genevieve; Da Cunha, Carla; Gamblin, Camille; Suffee, Nadine; Rouault, Christine; Leclerc, Arnaud; Lacombe, Amelie; Sokolovska, Nataliya; Gautier, Emmanuel L.; Clément, Karine; Dugail, Isabelle
ABSTRACT: Adipose tissue (AT) fibrosis in obesity compromises adipocyte functions and responses to intervention-induced weight loss. It is driven by AT progenitors with dual fibro/adipogenic potential, but pro-fibrogenic pathways activated in obesity remain to be deciphered. To investigate the role of macroautophagy/autophagy in AT fibrogenesis, we used Pdgfra-Cre Ert2 transgenic mice to create conditional deletion of Atg7 alleles in AT progenitor cells ( atg7 cKO) and examined sex-dependent, depot-specific AT remodeling in high-fat diet (HFD)-fed mice. Mice with atg7 cKO had markedly decreased extracellular matrix (ECM) gene expression in visceral, subcutaneous, and epicardial adipose depots compared to Atg7 lox/lox littermates. ECM gene program regulation by autophagy inhibition occurred independently of changes in the mass of fat tissues or adipocyte numbers of specific depots, and cultured preadipocytes treated with pharmacological or siRNA-mediated autophagy disruptors could mimic these effects. We found that autophagy inhibition promotes global cell-autonomous remodeling of the paracrine TGF-BMP family landscape, whereas ECM gene modulation was independent of the autophagic regulation of GTF2IRD1. The progenitor-specific mouse model of ATG7 inhibition confirms the requirement of autophagy for white/beige adipocyte turnover, and combined to in vitro experiments, reveal progenitor autophagy dependence for AT fibrogenic response to HFD, through the paracrine remodeling of TGF-BMP factors balance. Abbreviations: CQ: chloroquine; ECM: extracellular matrix; EpiAT: epididymal adipose tissue; GTF2IRD1: general transcription factor II I repeat domain-containing 1; HFD: high-fat diet; KO: knockout; OvAT: ovarian adipose tissue; PDGFR: platelet derived growth factor receptor; ScAT: subcutaneous adipose tissue; TGF-BMP: transforming growth factor-bone morphogenic protein